Mimotopes of the Vi antigen of Salmonella enterica serovar Typhi identified from phage display peptide library - Tang, Swee-Seong; Tan, Wen-Siang; Devi, Shamala; Wang, Lin-Fa; Pang, Tikki; Thong, Kwai-Lin (American Society for Microbiology, 2003)
The capsular polysaccharide Vi antigen (ViCPS) is an essential virulence factor and also a protective antigen of Salmonella enterica serovar Typhi. A random 12-mer phage-displayed peptide library was used to identify mimotopes (epitope analogues) of this antigen by panning against a ViCPS-specific monoclonal antibody (MAb) ATVi. Approximately 75% of the phage clones selected in the fourth round carried the peptide sequence TSHHDSHGLHRV, and the rest of the clones harbored ENHSPVNIAHKL and other related sequences. These two sequences were also obtained in a similar panning process by using pooled sera from patients with a confirmed diagnosis of typhoid fever, suggesting they mimic immunodominant epitopes of ViCPS antigens. Binding of MAb ATVi to the mimotopes was specifically blocked by ViCPS, indicating that they interact with the same binding site (paratope) of the MAb. Data and reagents generated in this study have important implications for the development of peptide-base diagnostic tests and peptide vaccines and may also provide a better understanding of the pathogenesis of typhoid fever.